Funcionalidade pré-operatória e desfechos pós-operatórios em indivíduos submetidos a cirurgia cardíaca: existe relação? - Lira, Carolina Azevedo da Graça (2025)
Introduction: Cardiac surgery is an effective way to treat serious heart diseases that cannot be treated with conservative measures. However, the surgical approach can cause a series of clinical and functional complications, with pulmonary complications being the most common. Postoperative pulmonary complications can occur due to several factors related to the surgical procedure or the patient, including low preoperative functional reserve. Therefore, it is important to perform a preoperative evaluation to outline strategies to avoid postoperative complications. Objective: To investigate the association between preoperative functionality and the occurrence of complications and length of hospital stay in individuals undergoing cardiac surgery. Methods: Observational and prospective study carried out at the Walter Cantídio University Hospital (WCUH), with 82 patients undergoing cardiac surgery from November 2020 to July 2024. The sample consisted of patients admitted for elective cardiac surgery following the inclusion and exclusion criteria of the study. The data collected were: sociodemographic, anthropometric and clinical characteristics, functionality according to the World Health Organization Disability Assessment Schedule (WHODAS 2.0), health-related quality of life according to EQ-5D-5L, lung function according to slow vital capacity (SVC) and maximum phonation time (MPT), upper limb physical capacity according to the 1-minute arm elevation test (1BST) and handgrip strength (HGS), and functional mobility according to the Timed Up and Go at maximum speed (TUGmax). All assessments were performed in the preoperative period. Post-surgical complications were analyzed by the emergence of clinical disorders from the first day after surgery until hospital discharge. Logistic regression analyses for the outcome post-operative complications and linear regression for length of hospital stay were applied using SPSS 24.0. Results: The majority were women (56%), with a median age of 62 years, undergoing cardiac surgery for the first time (88%). The majority did not perform regular physical activity (85%) and almost half of the study population were smokers (47%). 44 patients (54%) presented at least one complication in the postoperative period, with atelectasis and pleural effusion being the most common complications. In univariate logistic regression, SVC (p=0.04) and MPT (p<0.0001) were related to complications, but in multivariate regression only MPT (p=0.01) was shown to be a predictor of complications in the postoperative period (OR=0.92). Regarding the predictor of hospitalization time in univariate linear regression, the length of stay in the ICU (p=0.002), FMR (p<0.001) and WHODAS 2.0 (p=0.008) showed a relationship, but only the length of days in the ICU (p=0.002; β=5.7) and MPT (p=0.01; β=-0.57) were shown to be predictors. Conclusion: A relationship was observed between preoperative functionality and postoperative outcomes, with MPT being a predictor of both complications and length of hospital stay for patients undergoing cardiac surgery.